Muon capture on light isotopes measured with the Double Chooz detector - Abe, Y.; Abrahão, T.; Almazan, H.; Alt, C.; Appel, S.; Barriere, J. C.; Baussan, E.; Bekman, I.; Bergevin, M.; Bezerra, T. J. C.; Bezrukov, L.; Blucher, E.; et al. (My University, 2016)
Using the Double Chooz detector, designed to measure the neutrino mixing angle ?13, the products of ?- capture on C12,C13,N14, and O16 have been measured. Over a period of 489.5 days, 2.3×106 stopping cosmic ?- have been collected, of which 1.8×105 captured on carbon, nitrogen, or oxygen nuclei in the inner detector scintillator or acrylic vessels. The resulting isotopes were tagged using prompt neutron emission (when applicable), the subsequent ? decays, and, in some cases, ?-delayed neutrons. The most precise measurement of the rate of C12(?-,?)B12 to date is reported: 6.57-0.21+0.11×103s-1, or (17.35-0.59+0.35)% of nuclear captures. By tagging excited states emitting ?s, the ground state transition rate to B12 has been determined to be 5.68-0.23+0.14×103s-1. The heretofore unobserved reactions C12(?-,??)Li8,C13(?-,?n?)Li8, and C13(?-,?n)B12 are measured. Further, a population of ?n decays following stopping muons is identified with 5.5? significance. Statistics limit our ability to identify these decays definitively. Assuming negligible production of He8, the reaction C13(?-,??)Li9 is found to be present at the 2.7? level. Limits are set on a variety of other processes. © 2016 American Physical Society.
Citation: Abe, Y., Abrahão, T., Almazan, H., Alt, C., Appel, S., Barriere, J. C., . . . Zimmer, V. (2016). Muon capture on light isotopes measured with the Double Chooz detector. Physical Review C - Nuclear Physics, 93(5). doi:10.1103/PhysRevC.93.054608
Additional Authors: Buck, C.;Busenitz, J.;Cabrera, A.;Camilleri, L.;Carr, R.;Cerrada, M.;Chauveau, E.;Chimenti, P.;Collin, A. P.;Conover, E.;Conrad, J. M.;Crespo-Anadón, J. I.;Crum, K.;Cucoanes, A. S.;Damon, E.;Dawson, J. V.;De Kerret, H.;Dhooghe, J.;Dietrich, D.;Djurcic, Z.;Dos Anjos, J. C.;Dracos, M.;Etenko, A.;Fallot, M.;Felde, J.;Fernandes, S. M.;Fischer, V.;Franco, D.;Franke, M.;Furuta, H.;Gil-Botella, I.;Giot, L.;Göger-Neff, M.;Gomez, H.;Gonzalez, L. F. G.;Goodenough, L.;Goodman, M. C.;Haag, N.;Hara, T.;Haser, J.;Hellwig, D.;Hofmann, M.;Horton-Smith, G. A.;Hourlier, A.;Ishitsuka, M.;Jochum, J.;Jollet, C.;Kaether, F.;Kalousis, L. N.;Kamyshkov, Y.;Kaneda, M.;Kaplan, D. M.;Kawasaki, T.;Kemp, E.;Kryn, D.;Kuze, M.;Lachenmaier, T.;Lane, C. E.;Lasserre, T.;Letourneau, A.;Lhuillier, D.;Lima, H. P., Jr.;Lindner, M.;López-Castaño, J. M.;Losecco, J. M.;Lubsandorzhiev, B.;Lucht, S.;Maeda, J.;Mariani, C.;Maricic, J.;Martino, J.;Matsubara, T.;Mention, G.;Meregaglia, A.;Miletic, T.;Milincic, R.;Minotti, A.;Nagasaka, Y.;Navas-Nicolás, D.;Novella, P.;Oberauer, L.;Obolensky, M.;Onillon, A.;Osborn, A.;Palomares, C.;Pepe, I. M.;Perasso, S.;Porta, A.;Pronost, G.;Reichenbacher, J.;Reinhold, B.;Röhling, M.;Roncin, R.;Rybolt, B.;Sakamoto, Y.;Santorelli, R.;Schilithz, A. C.;Schönert, S.;Schoppmann, S.;Shaevitz, M. H.;Sharankova, R.;Shrestha, D.;Sibille, V.;Sinev, V.;Skorokhvatov, M.;Smith, E.;Soiron, M.;Spitz, J.;Stahl, A.;Stancu, I.;Stokes, L. F. F.;Strait, M.;Suekane, F.;Sukhotin, S.;Sumiyoshi, T.;Sun, Y.;Svoboda, R.;Terao, K.;Tonazzo, A.;Trinh Thi, H. H.;Valdiviesso, G.;Vassilopoulos, N.;Veyssiere, C.;Vivier, M.;Von Feilitzsch, F.;Wagner, S.;Walsh, N.;Watanabe, H.;Wiebusch, C.;Wurm, M.;Yang, G.;Yermia, F.;Zimmer, V.